Pengaruh Praktik Tata Kelola Perusahaan terhadap Kinerja Keuangan Perusahaan Non-Keuangan Dimediasi Manajemen Risiko - Peny Peny; Meiliana Meiliana (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The study was conducted to determine the effect of corporate governance components on financial performance mediated by risk management. In 2016-2020, non-financial sector companies on the IDX became the object of research. This research is quantitative by taking the data through financial reports. The technique applied to the research data testing is multiple linear analysis and path analysis. The results show that corporate governance practices such as auditor reputation, size of the board of commissioners, audit committee, board meetings, and financial reporting risk have a significant effect on financial performance where risk management acts as a mediation. Risk management is proven to have an effective influence in the company so that the management of corporate governance is better, and financial performance can be managed optimally. Risk management also helps to supervise and minimize any possible activities that will have an impact on causing risks, both internal and external risks.